Analisis Responsivitas Pelayanan Publik Di Rumah Tahanan Negara Kelas I Cabang Rumah Tahanan Komisi Pemberantasan Korupsi - Elma Nurjanah; Dedy Kusna Utama (Jurnal Ilmu Administrasi Publik, 2021)
The Corruption Eradication Commission (KPK) is a government institution that specifically has a role in eradicating corruption. Not only that, KPK has also a Detention Center (Rutan) as a place for public servants to serve corruption prisoners. The role of KPK in providing service responsiveness to prisoners is very important because the  slow  service  responsiveness  will  have  an  impact  on  several prisoners'  rights  which  are  regulated  in  the  law.  This  study  has objective to determine and explain the responsiveness of public services in the First Class State Detention Center, the Corruption Eradication Commission's State Detention Center. The method used in this research is descriptive qualitative using Zeithml theory, namely to determine the attitude and communication of service providers, speed of service, accuracy of service, accuracy in serving, timeliness of service, and the response of service providers to complaints of prisoners that affect the responsiveness of public services. against prisoners. The results of the study indicate that the responsiveness of public services has not been carried out optimally because several obstacles are still found in the service, namely in the communication style on the ability to respond which causes incidents of beatings by detainees to prison officers. In the speed  of  service  related  to  the  legal  process  for  the  extension  of detention that occurs at the District Court, High Court and Supreme Court levels, delays often occur and health services in the detention center are  not 24  hours, so  that emergency health services outside normal working hours are not handled as quickly as expected. Furthermore, the accuracy of service is also due to the fact that the Head of KPK’s Detention Center has not been appointed definitively so that he cannot decide on the authority in strategic matters, only administrative in nature. And another shortcoming is the timeliness of service, there are still obstacles in the distribution of goods entrusted to the family to detainees, which takes a long time.